The Effect of Learning Styles on Students' Mathematical Communication Ability - Tahir Tahir (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
This research is motivated by the low mathematical communication skills of students, where there are many factors that influence this, one of which is the student's learning style. This study aims to determine the effect of learning styles on students' mathematical communication skills. This type of research is ex-post-facto research and was conducted at SMA Negeri 1 Mawasangka using a sample of 52 students. From the results of the analysis carried out, it was found that there was a relationship between student learning styles and students' mathematical communication abilities. This was because rhit > rtab (0.38> 0.27), the relationship formed was a positive one-way relationship because of the positive rhit value. In addition, from the one-way ANOVA, it was found that Fcount> Ftable, it was concluded that there were differences in students' mathematical communication skills when viewed from their learning styles and this difference was significant. So it can be concluded that the learning style has an effect on students' mathematical communication skills, and this influence is a positive influence. Keywords: learning styles, mathematical communication skills, influence.